2000
DOI: 10.2131/jts.25.49
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of the effects of a single intratracheal instillation of surface activeagents on lung in rats.

Abstract: Pulmonary drug administration of most peptide/protein drugs is characterized by low bioavailability due to low permeability. Surface active agents have been tested as an absorption enhancer, but few studies have been carried out on the local toxicity of these additives. In the present study, to clarify the toxic effects of surface active agents on the lung, a relatively high concentration (1%) of polyoxyethylene 9 lauryl ether (Laureth-9) and sodium glycocholate (SGC) was given to rats in a single intratrachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Moreover, ionic surfactants in oral drug formulations present challenges such as incompatibilities with other ionic molecules, sensitivity to pH, salt or temperature changes, GIT irritation, and toxicity. A more serious issue with surfactants is that they can be toxic if used in excess [5] especially in inhalation products [22,23]. Therefore, surfactants should be used sparingly to minimize all potential negative impact or should be eliminated completely, if possible, for certain pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ionic surfactants in oral drug formulations present challenges such as incompatibilities with other ionic molecules, sensitivity to pH, salt or temperature changes, GIT irritation, and toxicity. A more serious issue with surfactants is that they can be toxic if used in excess [5] especially in inhalation products [22,23]. Therefore, surfactants should be used sparingly to minimize all potential negative impact or should be eliminated completely, if possible, for certain pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…One potential drawback to these formulations is that they contain excipients, which aid in manufacturing and aerosol performance, but may have unforeseen negative impacts on the long-term respiratory health of the patient 2, 17. Of particular concern are penetration enhancers, such as polyoxyethylene 9 lauryl ether and sodium glycocholate, which have been shown to induce acute inflammation in the lung 20. It may therefore be desirable to create an inhalable form of insulin that does not contain excipients so as to avoid any potential complications that might arise.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al 21) demonstrated that high dose surfactants could induce acute lung inflammation under higher concentrations. Although it is not examined whether this effect exists under normal concentrations, this study revealed the potential toxicological effect of surfactants.…”
Section: Discussionmentioning
confidence: 99%